Trade Integration in East Asia : The Role of China and Production Networks - Haddad, Mona (World Bank, Washington, DC, 2012)
Production networks have been at the heart of the recent growth in trade among East Asian countries. Fragmentation trade, reflected mainly in the trade in parts and components, is expanding more rapidly than the conventional trade in final goods. This is mainly due to the relatively more favorable policy setting for international production, agglomeration benefits arising from the early entry into this new form of specialization, considerable intercountry wage differentials in the region, lower trade and transport costs, and specialization in products exhibiting increasing returns to scale. The economic integration of China has deepened production fragmentation in East Asia, countering fears of crowding out other countries for international specialization. International production fragmentation in East Asia has intensified intraregional trade but has depended heavily on extraregional trade in final goods. While production networks centered on China have contributed significantly to growth in East Asia, they also breed vulnerabilities. They have not automatically led to technology spillovers and have led to an extreme interdependence across East Asian countries.